Siron Franco: pinturas em série - Frazão, Joscelina (1998)
This dissertation addresses contemporary art through the painting of Siron Franco and proposes an aesthetic reading of his work, emphasizing the most important phases of his artistic career and demonstrating the transformations of his work. The selected paintings comprehend his career, from the beginning, in the seventies, up to his latest works, reflecting his vast trajectory and allowing a vision of his painting as a whole. From the work and the documentation existent on the author, we tried to identify his ceative process, his chief iconographic elements and his correlations with the brazilian artistic and cultural scene.